2013
DOI: 10.1016/j.ygcen.2013.07.017
|View full text |Cite
|
Sign up to set email alerts
|

AVT is involved in the regulation of ion transport in the intestine of the sea bream (Sparus aurata)

Abstract: The intestine of marine fish plays a crucial role in ion homeostasis by selective processing of ingested fluid. Although arginine vasotocin (AVT) is suggested to play a role in ion regulation in fish, its action in the intestine has not been demonstrated. Thus, the present study investigated in vitro the putative role of AVT in intestinal ion transport in the sea bream (Sparus aurata). A cDNA encoding part of an AVT receptor was isolated and phylogenetic analysis revealed it clustered with the V1a2-type recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…In addition, treatment of S. aurata with AVT and their subsequent transfer to different salinity conditions enhanced plasma cortisol level, gill and kidney Na + ,K + -ATPase activities and metabolism rate at plasma and tissue levels, reinforcing the idea of a hypoosmoregulatory role for AVT in this species (Sangiao-Alvarellos et al, 2006). Moreover, the effects of those hormones on several osmoregulatory epitheliums, such as gills, kidney or gastrointestinal tract, have been already reported in other species by their actions on ion absorption/secretion, urine production or glomerular filtration (Maetz et al, 1964;Motais and Maetz, 1967;Henderson and Wales, 1974;Amer and Brown, 1995;Martos-Sitcha et al, 2013).…”
Section: Introductionmentioning
confidence: 66%
“…In addition, treatment of S. aurata with AVT and their subsequent transfer to different salinity conditions enhanced plasma cortisol level, gill and kidney Na + ,K + -ATPase activities and metabolism rate at plasma and tissue levels, reinforcing the idea of a hypoosmoregulatory role for AVT in this species (Sangiao-Alvarellos et al, 2006). Moreover, the effects of those hormones on several osmoregulatory epitheliums, such as gills, kidney or gastrointestinal tract, have been already reported in other species by their actions on ion absorption/secretion, urine production or glomerular filtration (Maetz et al, 1964;Motais and Maetz, 1967;Henderson and Wales, 1974;Amer and Brown, 1995;Martos-Sitcha et al, 2013).…”
Section: Introductionmentioning
confidence: 66%
“…Several aspects of the vasotocinergic and isotocinergic systems have been previously characterised in the gilthead sea bream (S. aurata), and these systems have been putatively linked to several physiological processes, including osmoregulation Martos-Sitcha et al, 2013a;Martos-Sitcha et al, 2013b;Martos-Sitcha et al, 2014a), metabolism (Sangiao-Alvarellos et al, 2004;Sangiao-Alvarellos et al, 2006), and stress due to starvation and high stocking density (Mancera et al, 2008). However, relatively few studies have examined the link between stress pathway activation by cortisol and the vasotocinergic and isotocinergic systems.…”
Section: Discussionmentioning
confidence: 99%
“…In S. aurata, it has been demonstrated that AVT has regulatory effects on several molecular components of chloride cells, including the Na + /K + -ATPase pump (NKA), the cystic fibrosis transmembrane conductance regulator (CFTR) and the apical co-transporter Na + /K + /2Cl -(NKCC2), with the intracellular pathways of these receptors and ion transporters being shared (Martos-Sitcha et al, 2013a;Martos-Sitcha et al, 2014a). In fact, the development and proliferation of chloride cells, the increased NKA activity observed in several teleosts (McCormick, 1995;McCormick, 2012;Mancera et al, 2002;Laiz-Carrión et al, 2003) and the phenomenon of chloride secretion during episodes of chronic stress (Guibbolini et al, 1988;Martos-Sitcha et al, 2014a) support these conclusions.…”
Section: Gillmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sea bream, AVT treatment enhanced gill Na + ,K + -ATPase activity after hyperosmotic challenge (SangiaoAlvarellos et al, 2006). Also, we have recently shown an enhancement in absorptive pathways mediated by AVT in the regulation of a bumetanide sensitive mechanism, likely NKCC co-transporter, in the intestine of sea bream (Martos-Sitcha et al, 2013).…”
Section: Introductionmentioning
confidence: 88%